PENGARUH PEMBINAAN PENGAWAS DAN KEGIATAN MGMP TERHADAP KEMAMPUAN GURU PAI DALAM MELAKSANAKAN KURIKULUM 2013 - Zumfiardi Zumfiardi (Turast: Jurnal Penelitian dan Pengabdian, 2018)
This study aims to describe and analyze the influence of supervisors' training and PAI Teacher Subject deliberation activities on the ability of PAI Teachers to implement the 2013 Curriculum. This research was a field research type by using quantitative approach and associative methods. Respondents in this study were PAI Junior High School teachers in Padang. The findings of the study show that the guidance of supervisors to PAI teachers has a positive and significant effect on the ability of PAI teachers to implement the 2013 curriculum that is equal to 0.200 or 20.0%. PAI Subject Teachers' Meeting (MGMP) has a positive and significant effect on the ability of PAI teachers to implement the 2013 curriculum of 0.208 or 20.8%. Whereas supervisory guidance for PAI teachers and PAI Teacher Subject Meeting (MGMP) activities simultaneously had an influence on the ability of PAI teachers to implement the 2013 curriculum in SMPs in Padang City by 0.281 or 28.1%. It is concluded that the guidance of school supervisors and the activities of the subject teacher deliberations had a positive influence on the ability of religious teachers to implement the 2013 curriculum. This implies that coaching needs to be empowered intensively.